Design and development of a fiber bragg grating-based technique for interface pressure measurement inside below-knee prosthetic sockets / Ebrahim Ali Ahmed Al-Fakih - Ebrahim Ali , Ahmed Al-Fakih (2015)
Limb amputation is a surgical procedure performed to remove a whole or a part of a limb in an attempt to save the residual limb from any further damage. Amputees typically use artificial limbs (also called “prostheses”) as rehabilitation tools to restore their daily activities and cosmetic appearance. Unfortunately, almost all amputees are dissatisfied with their existing prostheses because of the poor fitting of prosthetic sockets. Despite the considerable advances in the pressure measurement techniques employed over the past five decades to map pressure distribution within prosthetic sockets, these techniques still exhibit several limitations, including their bulkiness (i.e., strain gauge transducers) and vulnerability to hysteresis, drift, and creases (i.e., piezoresistive and capacitive transducers). Therefore, developing a new technique that offers valid and reliable pressure measurement within prosthetic sockets is deemed necessary to help prosthetic professionals fabricate better-designed sockets that provide a good fit and amputee’s satisfaction. This research aims to investigate the feasibility of optical fiber Bragg grating (FBG) sensors as a potential alternative to the aforementioned techniques to spot peak pressures within prosthetic sockets. First, a single FBG flexible sensing pad was designed and evaluated at the anterior proximal region of the residual limb to assess its performance in dynamic conditions. This sensor was tested in real time by inserting a heavy-duty balloon into the socket and inflating/deflating it using an air compressor to mimic the actual amputee’s gait. Promising results in terms of sensitivity, accuracy, and hysteresis were obtained. These findings encouraged me to fabricate a series of FBG sensing pads with full consideration of three key fabrication parameters: different FBG embedding depth, sensing pad thickness, and host material hardness. Results revealed that the FBGs embedded in the neutral layer of hard and thick sensing pads exhibited the highest sensitivity and excellent accuracy. This concept was subsequently employed to fabricate four new expandable sensing pads with at least two sensing sites each to cover the proximal and distal sub-regions of each socket aspect. An amputee was involved to evaluate the in situ performance of this technique. The results were compared with the pressure measurements obtained using the commercially available F-socket sensors to validate the findings. The results revealed the advantages of the new sensor design as it could successfully detect all the events of an amputee’s gait. Higher pressure values were logged by the FBG sensors compared with the F-socket, which was attributed to the thickness of the sensor. However, the trend on pressure changes was similar for both sensor types. Eliminating the thickness drawback was achieved by embedding an array of FBGs within a custom fabricated silicone liner that is typically inserted in prosthetic sockets to cushion the transfer of loads from the socket to the residual limb. This FBG instrumented liner was designed so it could function both as a cushioning material and a sensing tool. No previous studies have implemented such a technique in prosthetic applications. Therefore, this research was the first investigation into the potential use of such a technique in prosthetic applications.